'The Above Mentioned Aliens': Rudolf Mersy's German Band in New Zealand, 1913–1919. Issue 1 (2nd January 2017) - Owens, Samantha
Abstract : In early August 1914—within a fortnight of the outbreak of World War I—Auckland police arrested twenty-four German nationals and sent them for internment in Wellington. Strikingly, twelve of these so-called 'enemy aliens' comprised a German band led by Rudolf Mersy (1867–1949), a composer renowned in his homeland as the 'Aschbacher Mozart'. Drawing upon previously restricted files held at Archives New Zealand (Wellington), this article uncovers the origins of these musicians, their activity in New Zealand prior to the advent of war, and the circumstances surrounding their internment. Somewhat surprisingly, given the cramped (and at times brutal) conditions on Somes Island, Mersy and his fellow bandsmen continued to be active as musicians throughout their captivity. The extant documents, which include official reports and confiscated letters written by the Prisoners of War (POWs) to family members, also reveal poignant details concerning their daily lives. Yet despite their earlier successes as touring musicians, in the immediate aftermath of the war lingering anti-German sentiment and the advent of recorded sound combined to ensure the disappearance of the once perennially popular German Band from the global musical scene.